Saint John Longshoremen During the Rise of Canada's Winter Port, 1895-1922 - Babcock, Robert (Labour/Le Travailleur, 1990)
Abstract During the 19th century a longshoring tradition emerged out of the booming lumber trade in Saint John. Shiplabourers' organizations periodically vied with local merchants for control of the waterfront casual labour market Work-bred feelings of mutualism were frequently undermined by job, ethnic, and religious segmentation. Despite the introduction of steamers, the longshore labour process remained relatively unchanged. The situation changed at the turn of the century as a result of the establishment of Saint John's winter-port facility. Big Capital confronted Big Labour in an all-out struggle for control of the docks. Aided by wartime conditions, the longshoremen finally succeeded in imposing new work-rules and exerting partial control over hiring practices. But after the Armistice, the shipping industry regained its previous authority, and hard-pressed Saint John longshoremen subsequently abandoned their class-based efforts in favour of regional political nostrums.